A Low-Noise, High-Gain, and Small-Size UWB Mixer Utilizing Negative Impedance Technique and Source Input Method - Zhaokun Zhou (MDPI AG, 2021)
This paper presents an ultra-wideband (UWB) down-conversion mixer with low-noise, high-gain and small-size. The negative impedance technique and source input method are applied for the proposed mixer. The negative impedance achieves the dynamic current injection and increases the mixer output impedance, which reduces the mixer flicker noise and increases its conversion gain. The source input method allows the input matching networks to be cancelled, avoiding the noise and loss introduced by the matching resistors, saving the chip area occupied by the matching inductors. The proposed mixer is designed in 45-nm SOI process provided by GlobalFoundries. The simulation results show a conversion gain of 11.4–14.3 dB, ranging from 3.1 to 10.6 GHz, a minimum noise figure of 9.8 dB, a RF port return loss of less than −11 dB, a port-to-port isolation of better than −48 dB, and a core chip area of 0.16 × 0.16 mm2. The power consumption from a 1 V supply voltage is 2.85 mW.